Electrolytic capacitors
A conductive polymer-based solid electrolyte layer with a balanced electrolyte composition stabilizes the electrolytic solution, addressing deterioration issues and maintaining reliability in electrolytic capacitors.
Patent Information
- Application Number
- JP2023152282
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-21
- Filing Date
- 2023-09-20
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2039-05-20
AI Technical Summary
The electrolytic solution in existing electrolytic capacitors deteriorates, leading to a risk of increased leakage current and deterioration of the dielectric layer, compromising the reliability of the capacitor.
Incorporating a conductive polymer-based solid electrolyte layer with a specific electrolyte composition containing an amidine as a first base component, a composite of inorganic and organic acids, and additional acid components like boric acid, phosphoric acid, and phosphorous acid, along with a carefully controlled pH range, to stabilize the electrolyte and prevent deterioration.
The solution enhances the reliability of electrolytic capacitors by maintaining the integrity of the dielectric layer and reducing leakage current, even under long-term use and thermal stress.
Smart Images

Figure 0007607227000003 
Figure 0007607227000004 
Figure 0007607227000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrolytic capacitor having a solid electrolyte layer containing a conductive polymer. [Background technology]
[0002] Electrolytic capacitors, which include an anode body having a dielectric layer and a solid electrolyte layer formed so as to cover at least a portion of the dielectric layer, are considered to be promising as small-sized, large-capacity capacitors with low equivalent series resistance (ESR).
[0003] Patent Document 1 discloses that in order to increase the voltage resistance of the electrolytic capacitor, a composite compound of an inorganic acid and an organic acid and an ammonium salt are used as a solute in the electrolyte. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2015-165550 A Summary of the Invention [Problem to be solved by the invention]
[0005] Patent Document 1 proposes that an electrolyte solution containing a composite compound of an inorganic acid and an organic acid and an ammonium salt be contained as a solute in the electrolyte solution.
[0006] However, in the electrolytic capacitor described in Patent Document 1, there is a risk that the electrolyte will deteriorate and the restorability of the dielectric layer of the electrolytic capacitor will no longer be maintained, resulting in an increase in leakage current. [Means for solving the problem]
[0007] In view of the above, one aspect of the present invention relates to an electrolytic capacitor including an anode element having a dielectric layer formed on a surface thereof, a solid electrolyte layer in contact with the dielectric layer and including a conductive polymer, and an electrolyte solution including an amidine compound as a first base component, a composite compound of an inorganic acid and an organic acid as a first acid component, and at least one acid selected from boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, and phosphonic acid as a second acid component. Effect of the Invention
[0008] According to the present invention, it is possible to provide an electrolytic capacitor with excellent reliability. [Brief description of the drawings]
[0009] [Figure 1] 1 is a schematic cross-sectional view of an electrolytic capacitor according to one embodiment of the present invention. [Diagram 2] 2 is a schematic diagram for explaining the configuration of a capacitor element according to the same embodiment. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in more detail below based on the embodiments, however, the present invention is not limited to the following embodiments.
[0011] FIG. 1 is a schematic cross-sectional view of the electrolytic capacitor according to this embodiment, and FIG. 2 is a schematic exploded view of a portion of a capacitor element of the electrolytic capacitor.
[0012] The electrolytic capacitor includes, for example, a capacitor element 10, a bottomed case 11 that houses the capacitor element 10, a sealing member 12 that closes the opening of the bottomed case 11, a seat plate 13 that covers the sealing member 12, lead wires 14A, 14B that are led out from the sealing member 12 and pass through the seat plate 13, lead tabs 15A, 15B that connect the lead wires to electrodes of the capacitor element 10, and an electrolyte (not shown) that contains an electrolytic solution and a solid electrolyte. The vicinity of the open end of the bottomed case 11 is drawn inward, and the open end is curled so as to be crimped to the sealing member 12.
[0013] Capacitor element 10 is produced from a wound body as shown in Fig. 2. The wound body includes an anode body 21 connected to lead tab 15A, a cathode body 22 connected to lead tab 15B, and a separator 23. The wound body is a semi-finished product in which a solid electrolyte layer is not formed between anode body 21 and cathode body 22.
[0014] Anode body 21 and cathode body 22 are wound with separator 23 interposed therebetween. The outermost periphery of the wound body is fixed with stop tape 24. Note that Fig. 2 shows a state in which the wound body is partially unfolded before the outermost periphery is fixed. The material of separator 23 can be, for example, a nonwoven fabric containing cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like as a main component.
[0015] Anode body 21 comprises a metal foil whose surface has been roughened to have projections and recesses, and a dielectric layer is formed on the metal foil having projections and recesses. A conductive polymer is attached to at least a portion of the surface of the dielectric layer to form a solid electrolyte layer. The solid electrolyte layer may cover at least a portion of the surface of cathode body 22 and / or the surface of separator 23. Capacitor element 10 with the solid electrolyte layer formed thereon is housed in an exterior case together with an electrolytic solution.
[0016] The conductive polymer contained in the solid electrolyte layer is a π-conjugated conductive polymer, and polypyrrole, polythiophene, polyaniline, etc. are preferable. In this specification, polypyrrole, polythiophene, polyaniline, etc. refer to polymers having polypyrrole, polythiophene, polyaniline, etc. as their basic skeletons, respectively. Therefore, polypyrrole, polythiophene, polyaniline, etc. may also include their respective derivatives. For example, polythiophene includes its derivative, poly(3,4-ethylenedioxythiophene) (PEDOT), etc. These may be used alone, or in combination of two or more kinds, or may be copolymers of two or more kinds of monomers. The weight-average molecular weight of the conductive polymer is not particularly limited, but is, for example, 1000 to 100000. The solid electrolyte layer may further include a dopant.
[0017] The electrolyte solution of the present embodiment includes a solvent, a first base component, a first acid component, and a second acid component.
[0018] The solvent preferably contains a glycol compound. Examples of the glycol compound include alkylene glycol and polyalkylene glycol having a weight average molecular weight of 300 or less. More specifically, examples of the glycol compound include ethylene glycol, propylene glycol, butylene glycol, pentylene glycol, hexylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, pentaethylene glycol, and hexaethylene glycol. These may be used alone or in combination of two or more. Among them, glycol compounds having a molecular weight of 300 or less, such as ethylene glycol, propylene glycol, butylene glycol (butanediol), and pentylene glycol (pentanediol), have low viscosity among glycol compounds, so that they easily dissolve solutes, have high thermal conductivity, and are also excellent in heat dissipation when a ripple current is generated, so that heat resistance can be improved. Among them, ethylene glycol has a large effect of improving heat resistance.
[0019] Furthermore, the solvent may contain a sulfone compound. The sulfone compound is an organic compound having a sulfonyl group (-SO2-) in the molecule. Examples of the sulfone compound include chain sulfone and cyclic sulfone. Examples of the chain sulfone include dimethyl sulfone, diethyl sulfone, dipropyl sulfone, and diphenyl sulfone. Examples of the cyclic sulfone include sulfolane, 3-methyl sulfolane, 3,4-dimethyl sulfolane, and 3,4-diphenylmethyl sulfolane. Among them, from the viewpoint of dissociation property and thermal stability of the solute, the sulfone compound is preferably sulfolane. Since sulfolane has a low viscosity among sulfone compounds, it is easy to dissolve the solute.
[0020] Examples of other components of the solvent include lactone compounds and carbonate compounds. Examples of lactone compounds include γ-butyrolactone (GBL) and γ-valerolactone. Examples of carbonate compounds include dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC). These may be used alone or in combination of two or more. Among these, from the viewpoint of thermal stability, it is preferable that the other component is a lactone compound, and GBL is more preferable.
[0021] The first base component includes an amidine compound. The amidine compound is a compound having an alkyl-substituted amidine group, and examples thereof include cyclic amidine compounds or quaternized compounds thereof (amidinium compounds). Specific examples thereof include imidazoline compounds, imidazole compounds, benzimidazole compounds, and alicyclic pyrimidine compounds quaternized with an alkyl group or arylalkyl group having 1 to 11 carbon atoms. More specifically, 1-methyl-1,8-diazabicyclo[5,4,0]undecene-7, 1-methyl-1,5-diazabicyclo[4,3,0]nonene-5, 1,2,3-trimethylimidazolinium, 1,2,3,4-tetramethylimidazolinium, 1,3-dimethyl-2-ethyl-imidazolinium, 1,3,4-trimethyl-2-ethylimidazolinium, 1,3-dimethyl-2-heptylimidazolinium, 1,3-dimethyl-2-(-3'heptyl)imidazolinium, 1,3-dimethyl-2-dodecylimidazolinium, 1,2,3-trimethyl-1,4,5,6-tetrahydropyrimidium, 1,3-dimethylimidazolium, 1,3-dimethylbenzimidazolium, and the like can be mentioned.
[0022] The first acid component includes a composite compound of an organic acid and an inorganic acid. As the composite compound of an organic acid and an inorganic acid, borodisalicylic acid, borodioxalic acid, borodiglycolic acid, etc., which have high heat resistance, are preferable.
[0023] The second acid component contains at least one selected from boric acid, phosphoric acid, phosphorous acid, hypophosphorous acid, and phosphonic acid. The second acid component may be esterified. For example, the esterified product of the second acid component may be a condensate of a part of the hydroxyl group of the second acid component with an alcohol compound, a glycol compound, or the like.
[0024] An electrolyte solution containing a composite compound of an organic acid and an inorganic acid as a first acid component tends to have a high acidity. However, in this embodiment, the first base component contains an amidine compound, which has a higher basicity than amine compounds such as primary amine compounds, secondary amine compounds, and tertiary amine compounds, so the pH of the electrolyte solution does not become too low. Therefore, the corrosion of the anode body can be suppressed, and the reliability of the electrolytic capacitor can be improved.
[0025] In addition, by including the second acid component in the electrolytic solution, the decomposition of the first acid component can be suppressed. Therefore, in an electrolytic capacitor in which a solid electrolyte layer containing a conductive polymer is in contact with a dielectric layer, the deterioration of the electrolytic solution can be suppressed, and the restorability can be maintained even during long-term use, so that an increase in leakage current can be suppressed. From the viewpoint of suppressing the decomposition of the first acid component, boric acid is preferable as the second acid component. In addition, the second acid component may be esterified in the electrolytic solution.
[0026] In the electrolytic solution, the total amount of the first base component and the first acid component is preferably 5 wt% to 35 wt%, more preferably 5 wt% to 30 wt%. By setting the total amount in this range, in an electrolytic capacitor in which a solid electrolyte layer containing a conductive polymer is in contact with a dielectric layer, sufficient conductivity of the electrolytic solution can be obtained and the repairability of the dielectric layer can be improved.
[0027] In the electrolyte, the amount of the second acid component is preferably 0.1 wt% or more and 15 wt% or less. By making it 0.1 wt% or more, decomposition of the first acid component can be further suppressed. Also, by making it 15 wt% or less, precipitation of the second acid component in the electrolyte can be suppressed.
[0028] The electrolytic solution may further include a second base component. Examples of the second base component include primary amine compounds, secondary amine compounds, tertiary amine compounds, and quaternary ammonium compounds. Examples of the primary amine include methylamine, ethylamine, and propylamine. Examples of the secondary amine include dimethylamine, diethylamine, ethylmethylamine, and dibutylamine. Examples of the tertiary amine include trimethylamine, triethylamine, tributylamine, and ethyldiisopropylamine. Examples of the quaternary ammonium ion of the quaternary ammonium salt include tetramethylammonium, triethylmethylammonium, and tetraethylammonium. By including the second base component in the electrolytic solution, the pH of the electrolytic solution can be prevented from becoming too low.
[0029] The second base component is preferably weakly alkaline (eg, has a pH of 11 or less in an aqueous solution).
[0030] The second base component may be a primary to tertiary amine compound having a hydroxyl group. Examples of the primary to tertiary amine compound having a hydroxyl group include aliphatic primary to tertiary amine compounds, and in particular, aliphatic primary amine compounds are more preferable. Examples of the aliphatic primary amine compound having a hydroxyl group include weakly alkaline monomethanolamine, monoethanolamine, dihydroxymethylaminomethane, trishydroxymethylaminomethane, and the like. From the viewpoint of suppressing corrosion of the anode body, aliphatic primary amine compounds having two or more hydroxyl groups are preferable, and aliphatic primary amine compounds having three or more hydroxyl groups are more preferable. Examples of the aliphatic primary amine compound having three or more hydroxyl groups are trishydroxymethylaminomethane.
[0031] In the present embodiment, the pH of the electrolyte is preferably 1.5 to 5.5. When the conductive polymer contains a dopant, the pH is set to 5.5 or less to suppress the dopant from being de-doped from the conductive polymer, and the increase in ESR caused by the dopant de-doping is suppressed. In addition, the pH is set to 1.5 or more to suppress the corrosion of the anode body.
[0032] The pH of the electrolytic solution can also be adjusted by adding a second base component. The pH of the electrolytic solution to which the second base component has been added is preferably 1.5 or more and 5.5 or less. By including the second base component in the electrolytic solution, the pH of the electrolytic solution can be prevented from becoming too low. In addition, when an aliphatic primary amine compound is used as the second base component, the pH of the electrolytic solution can be prevented from becoming too high.
[0033] The electrolytic solution may contain a third acid component. As the third acid component, a nitro compound is preferable. As the nitro compound, a compound having a nitro group and a carboxyl group, a compound having a nitro group and a hydroxyl group, a compound having a nitro group and a hydroxyalkyl group, etc. can be mentioned. As the compound having a nitro group and a carboxyl group, for example, o-nitrobenzoic acid, m-nitrobenzoic acid, p-nitrobenzoic acid, nitrobenzenedicarboxylic acid, dinitrobenzenecarboxylic acid, nitrotoluenecarboxylic acid, nitroanisolecarboxylic acid, etc. can be mentioned. As the compound having a nitro group and a hydroxyl group, o-nitrophenol, m-nitrophenol, p-nitrophenol, p-nitroacetophenone, etc. can be mentioned. As the compound having a nitro group and a hydroxyalkyl group, o-nitrobenzyl alcohol, m-nitrobenzyl alcohol, p-nitrobenzyl alcohol, nitrobenzeneethanol, etc. can be mentioned. By including the third acid component in the electrolytic solution, the decomposition of the first acid component can be further suppressed. In the electrolytic solution, the amount of the third acid component is preferably 0.1 wt% or more and 15 wt% or less. By setting the content to 0.1 wt% or more, the decomposition of the first acid component can be further suppressed. Also, by setting the content to 15 wt% or less, the precipitation of the third acid component in the electrolyte can be suppressed. Among them, o-nitrobenzoic acid, m-nitrobenzoic acid, and p-nitrobenzoic acid are preferable as the third acid component because they can suppress the decomposition of the first acid component.
[0034] In the electrolytic capacitor of this embodiment, even if self-heating occurs during use due to, for example, ripple current, the decomposition of the first acid component can be further suppressed because the electrolytic capacitor contains the first acid component and the second acid component, and furthermore, the pH of the electrolytic solution does not become too low due to the first base component. Therefore, the electrolytic capacitor of this embodiment can suppress deterioration of the electrolytic solution due to heat, so that the repairability of the dielectric layer can be maintained and an increase in leakage current can be suppressed.
[0035] Hereinafter, an example of a method for manufacturing the electrolytic capacitor according to this embodiment will be described step by step. (i) preparing an anode body 21 having a dielectric layer First, prepare a metal foil as the raw material of the anode body 21. Although the type of metal is not particularly limited, it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal, because this facilitates the formation of a dielectric layer.
[0036] Next, the surface of the metal foil is roughened. By roughening, a plurality of projections and recesses are formed on the surface of the metal foil. The roughening is preferably performed by etching the metal foil. The etching may be performed by, for example, DC electrolysis or AC electrolysis.
[0037] Next, a dielectric layer is formed on the roughened surface of the metal foil. The method of formation is not particularly limited, but the dielectric layer can be formed by subjecting the metal foil to a chemical conversion treatment. In the chemical conversion treatment, for example, the metal foil is immersed in a chemical conversion solution such as an ammonium adipate solution and heat-treated. Alternatively, the metal foil may be immersed in the chemical conversion solution and a voltage may be applied.
[0038] Usually, from the viewpoint of mass production, a large-sized foil (metal foil) of a valve metal or the like is subjected to a surface roughening treatment and a chemical conversion treatment. In this case, the treated foil is cut to a desired size to prepare the anode body 21. (ii) Step of preparing cathode body 22 As with the anode body, a metal foil can be used for the cathode body 22. The type of metal is not particularly limited, but it is preferable to use a valve metal such as aluminum, tantalum, or niobium, or an alloy containing a valve metal. If necessary, the surface of the cathode body 22 may be roughened. In addition, a chemical conversion coating of about 2V or a metal coating of titanium, nickel, carbon, or the like may be formed on the surface of the cathode body 22. (iii) Preparation of the roll Next, a wound body is produced using the anode body 21 and the cathode body 22.
[0039] First, anode body 21 and cathode body 22 are wound with separator 23 interposed therebetween. At this time, lead tabs 15A, 15B are wound while being wound, so that lead tabs 15A, 15B can be planted from the wound body as shown in FIG.
[0040] The material of the separator 23 may be, for example, a nonwoven fabric containing natural cellulose, synthetic cellulose, polyethylene terephthalate, vinylon, aramid fiber, or the like as a main component.
[0041] The material of the lead tabs 15A and 15B is not particularly limited as long as it is a conductive material. The material of the lead wires 14A and 14B connected to the lead tabs 15A and 15B, respectively, is also not particularly limited as long as it is a conductive material.
[0042] Next, of the wound anode body 21, cathode body 22, and separator 23, a stop tape 24 is placed on the outer surface of cathode body 22, which is the outermost layer, and an end of cathode body 22 is fixed with stop tape 24. When anode body 21 is prepared by cutting a large-sized metal foil, a chemical conversion treatment may be further performed on the wound body in order to provide a dielectric layer on the cut surface of anode body 21. (iv) Step of forming capacitor element 10 Next, for example, the polymer dispersion is impregnated into the dielectric layer to form a film covering at least a part of the dielectric layer. The polymer dispersion includes a liquid component and a conductive polymer dispersed in the liquid component. The polymer dispersion may be a solution in which a conductive polymer is dissolved in the liquid component, or a dispersion in which particles of a conductive polymer are dispersed in the liquid component. Next, the liquid component is volatilized from the formed film by drying, thereby forming a dense solid electrolyte layer covering at least a part of the dielectric layer. Since the polymer dispersion is uniformly distributed in the liquid component, it is easy to form a uniform solid electrolyte layer. In this way, the capacitor element 10 is obtained.
[0043] The polymer dispersion can be obtained, for example, by dispersing a conductive polymer in a liquid component, or by polymerizing a precursor monomer in the liquid component to generate conductive polymer particles, etc. A preferred polymer dispersion is, for example, poly(3,4-ethylenedioxythiophene) (PEDOT) doped with polystyrene sulfonate (PSS), i.e., PEDOT / PSS.
[0044] The liquid component may be water, a mixture of water and a non-aqueous solvent, or a non-aqueous solvent. The non-aqueous solvent is not particularly limited, but for example, a protic solvent or an aprotic solvent can be used. Examples of the protic solvent include alcohols such as methanol, ethanol, propanol, butanol, ethylene glycol, and propylene glycol, and ethers such as formaldehyde and 1,4-dioxane. Examples of the aprotic solvent include amides such as N-methylacetamide, N,N-dimethylformamide, and N-methyl-2-pyrrolidone, esters such as methyl acetate, and ketones such as methyl ethyl ketone.
[0045] The step of applying the polymer dispersion to the surface of the dielectric layer and the step of drying the wound body may be repeated two or more times. By performing these steps multiple times, the coverage of the solid electrolyte layer on the dielectric layer can be increased. In this case, the solid electrolyte layer may be formed not only on the surface of the dielectric layer but also on the surfaces of the cathode body 22 and the separator 23.
[0046] In this manner, a solid electrolyte layer is formed between anode body 21 and cathode body 22, producing capacitor element 10. The solid electrolyte layer formed on the surface of the dielectric layer actually functions as a cathode material. (v) A step of preparing an electrolyte solution and impregnating the capacitor element 10 with the electrolyte solution. Next, the above-mentioned solutes (acid component and base component) are dissolved in a solvent to prepare an electrolytic solution, and then the capacitor element 10 is impregnated with the electrolytic solution. There are no particular limitations on the method for impregnating the capacitor element 10 with the electrolytic solution. For example, a method of immersing the capacitor element 10 in the electrolytic solution contained in a container is simple and preferable. The immersion time depends on the size of the capacitor element 10, but is, for example, 1 second to 5 minutes. The impregnation is preferably performed under reduced pressure, for example, in an atmosphere of 10 to 100 kPa, preferably 40 to 100 kPa. (vi) Encapsulating the capacitor element Next, capacitor element 10 is sealed. Specifically, capacitor element 10 is first housed in bottomed case 11 so that lead wires 14A and 14B are located on the upper surface of bottomed case 11, which is open. The material of bottomed case 11 can be a metal such as aluminum, stainless steel, copper, iron, brass, or an alloy of these metals.
[0047] Next, sealing member 12, which is formed so that lead wires 14A, 14B pass through it, is placed above capacitor element 10, and capacitor element 10 is sealed in bottomed case 11. Next, a horizontal drawing process is performed near the open end of bottomed case 11, and the open end is crimped to sealing member 12 to curl it. Then, seat plate 13 is placed on the curled portion, completing the electrolytic capacitor as shown in Fig. 1. Thereafter, an aging process may be performed while applying a rated voltage.
[0048] In the above embodiment, a wound-type electrolytic capacitor has been described, but the scope of application of the present invention is not limited to the above, and the present invention can also be applied to other electrolytic capacitors, for example, chip-type electrolytic capacitors that use a metal sintered body as an anode body, and stacked-type electrolytic capacitors that use a metal plate as an anode body. [Example] The present invention will be described in more detail with reference to examples, but the present invention is not limited to these examples.
[0049] In the following example, a wound electrolytic capacitor (Φ10 mm×L (length) 10 mm) with a rated voltage of 25 V and a rated capacitance of 330 μF was produced. A specific method for producing the electrolytic capacitor will be described below. (Preparation of anode body) An aluminum foil having a thickness of 100 μm was subjected to an etching treatment to roughen the surface of the aluminum foil. Then, a dielectric layer was formed on the surface of the aluminum foil by chemical conversion treatment. The chemical conversion treatment was performed by immersing the aluminum foil in an ammonium adipate solution and applying a voltage of 50 V to the aluminum foil. Then, the aluminum foil was cut to prepare an anode body. (Preparation of the cathode body) An aluminum foil having a thickness of 50 μm was subjected to an etching treatment to roughen the surface of the aluminum foil, and then the aluminum foil was cut to prepare a cathode body. (Making of the roll) An anode lead tab and a cathode lead tab were connected to the anode body and the cathode body, and the anode body and the cathode body were wound with the lead tabs interposed between them and a cellulose separator. An anode lead wire and a cathode lead wire were connected to the ends of the lead tabs protruding from the wound body, respectively. The wound body thus produced was subjected to a chemical conversion treatment again, and a dielectric layer was formed on the cut ends of the anode body. Next, the ends of the outer surface of the wound body were fixed with a winding stop tape to produce the wound body. (Preparation of polymer dispersion) 3,4-ethylenedioxythiophene and the polymer dopant polystyrene sulfonic acid (PSS, weight-average molecular weight 100,000) were dissolved in ion-exchanged water to prepare a mixed solution. Iron (III) sulfate (oxidant) dissolved in ion-exchanged water was added while stirring the mixed solution to carry out a polymerization reaction. After the reaction, the resulting reaction solution was dialyzed to remove unreacted monomers and excess oxidant, and a polymer dispersion containing polyethylenedioxythiophene doped with approximately 5% by mass of PSS (PEDOT / PSS) was obtained. (Formation of solid electrolyte layer) The wound body was immersed in a polymer dispersion contained in a specified container in a reduced pressure atmosphere (40 kPa) for 5 minutes, and then pulled out of the polymer dispersion. The wound body impregnated with the polymer dispersion was then dried in a drying oven at 150°C for 20 minutes to form a solid electrolyte layer made of a conductive polymer layer covering at least a part of the dielectric layer. (Electrolyte Impregnation) An electrolyte solution containing a first acid component, a first base component, a second acid component, a second base component, and various solvents in the composition shown in Table 1 was prepared, and the wound body was immersed in the liquid components for 5 minutes in a reduced pressure atmosphere (40 kPa).
[0050] [Table 1] (Sealing of capacitor elements) The capacitor element impregnated with the electrolytic solution was sealed to complete electrolytic capacitors (Examples 1 to 9, Comparative Examples 1 and 2) as shown in Fig. 1. Thereafter, an aging treatment was performed at 130°C for 2 hours while applying the rated voltage. [evaluation] For the obtained electrolytic capacitor, the initial leakage current X0 (LC) and the initial equivalent series resistance Y0 (ESR) were measured.
[0051] Next, to evaluate the long-term reliability, the devices were held at 145°C for 4000 hours while applying the rated voltage, and the rate of change in leakage current (ΔLC) and the rate of change in ESR (ΔESR) were confirmed.
[0052] ΔLC is shown as the ratio (X / X0) of LC(X) after holding at 145°C to the initial value (X0). The leakage current was measured after 120 seconds at room temperature after applying a voltage of 25V between the anode and cathode of the electrolytic capacitor.
[0053] ΔESR is expressed as the ratio (Y / Y0) of ESR (Y) after holding at 145°C to the initial value (Y0). Note that ESR was measured at a frequency of 100 kHz for the electrolytic capacitor using an LCR meter in a room temperature environment.
[0054] The evaluation results are shown in Table 2.
[0055] [Table 2] In comparison with Comparative Examples 1 and 2, Examples 1 to 9 were able to improve the reliability of the electrolytic capacitors. [Industrial Applicability]
[0056] The present invention can be used in an electrolytic capacitor comprising a solid electrolyte layer that covers at least a portion of a dielectric layer, and an electrolyte solution. [Explanation of symbols]
[0057] 10: capacitor element, 11: bottomed case, 12: sealing member, 13: seat plate, 14A, 14B: lead wires, 15A, 15B: lead tabs, 21: anode body, 22: cathode body, 23: separator, 24: winding stop tape
Claims
1. The anode body has a dielectric layer formed on a surface thereof, a solid electrolyte layer is in contact with the dielectric layer and contains a conductive polymer, and an electrolyte solution; The electrolyte solution includes a first base component, a first acid component, and a second acid component; the first base component comprises an amidine compound; The first acid component comprises a complex compound of an inorganic acid and an organic acid, The second acid component comprises at least one selected from phosphoric acid, phosphorous acid, hypophosphorous acid, and phosphonic acid; An electrolytic capacitor, wherein the content of the second acid component in the electrolytic solution is in the range of 15 wt % or less (excluding the case where the content of the second acid component is 2 wt % or less).
2. 2. The electrolytic capacitor of claim 1, wherein the first acid component comprises at least one selected from borodisalicylic acid, borodiglycolic acid, and borodisalic acid.
3. The electrolyte further comprises a second base component, 3. The electrolytic capacitor according to claim 1, wherein the second base component includes at least one selected from a primary amine compound, a secondary amine compound, a tertiary amine compound, and a quaternary ammonium compound.
4. The electrolyte solution includes a solvent, 4. The electrolytic capacitor according to claim 1, wherein the solvent includes a glycol compound.
5. 5. The electrolytic capacitor according to claim 4, wherein the weight average molecular weight of the glycol compound is 300 or less.
6. The electrolyte solution comprises a solvent, The electrolytic capacitor according to claim 1 , wherein the solvent contains a lactone compound.
7. The electrolytic capacitor of claim 6, wherein the lactone compound includes gamma-butyrolactone.
8. The electrolyte solution comprises a solvent, The electrolytic capacitor according to any one of claims 1 to 7, wherein the solvent contains a sulfone compound.
9. The electrolytic capacitor of claim 8, wherein the sulfone compound comprises sulfolane.
10. 10. The electrolytic capacitor according to claim 1, wherein a total content of the first base component and the first acid component in the electrolytic solution is in the range of 5 wt % to 30 wt %.
11. The electrolytic capacitor according to any one of claims 1 to 10, wherein the pH of the electrolytic solution is 1.5 or more and 5.5 or less.
12. The electrolyte further comprises a third acid component; The electrolytic capacitor according to any one of claims 1 to 11, wherein the third acid component comprises a nitro compound.
13. the second base component is the primary amine compound; 4. The electrolytic capacitor according to claim 3, wherein the primary amine compound is an aliphatic primary amine compound having a hydroxyl group.
14. The electrolytic capacitor according to claim 13 , wherein the aliphatic primary amine compound having a hydroxyl group has three or more hydroxyl groups.
Citation Information
Patent Citations
Aluminum electrolytic capacitor
JP2008098494A
Electrolytic solution for driving electrolytic capacitor and electrolytic capacitor using the same
JP2008177197A
Solid electrolytic capacitor and method of manufacturing the same
JP2015165550A
Electrolytic capacitor
WO2017163727A1